Jesus against the scribal elite: the origins of the conflict - Keith, Chris (T&T Clark, 2020)
"How did the controversy between Jesus and the scribal elite begin? We know that it ended on a cross, but what put Jesus on the radar of established religious and political leaders in the first place? Chris Keith argues this an answer to that question must go beyond typical explanations such as Jesus's alternative views on Torah or his miracle working and consider his status as a teacher"--